The path to the American Revolution : British-American relations in peace and war, 1721-1783 - Dull, Jonathan R., 1942- (New York, NY : Routledge, 2024)
"This book focuses on the gradual deterioration of the British-American relationship that led to the American Revolution. Starting in 1721, the author explores how the relationship between Britain and America changed from one of reciprocal trust, to one of mutual misunderstanding and suspicion. It analyses the impact of Britain's changing relationship with the other great powers of Europe, and discusses such matters as British concern about the national debt and French unease about Anglo-Russian cooperation. The book uniquely promotes the importance of foreign affairs in this disintegrating trans-Atlantic relationship and provides a concise introduction to the political and military aspects of American Revolution. This volume will be of interest to students of the American Revolution, and European and American foreign relations"--
Walpole's Britain Tolerates American Self-Rule, 1721-1739 -- War against Spain and France Destabilizes the Relationship, 1739-1754 -- The French and Indian War Endangers the Relationship, 1754-1763 -- The Aftermath of the War Dooms the Existing Relationship, 1763-1774 -- The War of American Independence Permanently Changes the Relationship, 1775-1783 -- Overview and Postscript.
Keywords: United States -- History -- Colonial period, ca. 1600-1775.; Great Britain -- Colonies -- America -- Administration; Great Britain -- Foreign relations -- 1714-1837.; Great Britain -- Politics and government -- 1727-1760.; Great Britain -- Politics and government -- 1760-1789.; United States -- History -- Revolution, 1775-1783 -- Causes; Great Britain -- Colonies -- America -- History -- 18th century; Great Britain -- Colonies -- Administration; HISTORY / General